Simulation of the Noise Transmission through Automotive Door Seals - Hazir, Andreas; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Vieweg, 2016)
Andreas Hazir is investigating the door seal contribution to the interior noise level of production vehicles. These investigations contain experimental contribution analyses of real production vehicles and of academic test cases as well as the development of a simulation methodology for noise transmission through sealing systems and side windows. The simulations are realized by coupling transient computational aeroacoustics of the exterior flow to nonlinear finite element simulations of the structural transmission. By introducing a linear transmission model, the setup and computational costs of the seal noise transmission are significantly reduced, resulting in the feasibility of numerical contribution analyses of real production vehicles. Contents Contribution Analyses of Production Vehicles Acoustic Excitation versus Aeroacoustic Excitation Development of a Simulation Methodology Sensitivity Analysis of Noise Transmission Simulations Target Groups Researchers and students in the field of automotive engineering Engineers in the field of vehicle acoustics, NVH, structural acoustics, and aeroacoustics About the Author After studying technomathematics at the Technical University of Munich, Andreas Hazir started his tenure as a research assistant in the vehicle acoustics department at the University of Stuttgart. In 2014, he joined the aerospace application management team of a software vendor for computational aeroacoustics (CAA). His main field of work involves CAA simulations of aircraft, rotorcraft, engines and liners.
Contribution Analyses of Production Vehicles -- Acoustic Excitation versus Aeroacoustic Excitation -- Development of a Simulation Methodology -- Sensitivity Analysis of Noise Transmission Simulations.
Keywords: Automotive engineering; Mechanics, Applied; Solids; Acoustical engineering; Automotive Engineering; Solid Mechanics; Engineering Acoustics